Artisanal production of the vinagreira cup liquor (Hibiscus sabdariffa L.) (Research, Society and Development, 2020)
Hibiscus sabdariffa L., commonly known as vinagreira, is a type of vegetable belonging to the family of Malvaceae, of the genus Hibiscus and comprising a wide variety of species. The artisanal production of liquors is an interesting alternative to increase family income, since its processing requires simple technology, the final product is sold at room temperature and has a long shelf life. The purpose of this study is the artisanal production of a liqueur based on the vinagreira (Hibiscus sabdariffa L.) The spaces used for this purpose will be the Dietary Technique and Food Sensory Analysis laboratories of the University Center for Science and Technology of Maranhão - UNIFACEMA, located in Caxias - MA. Sensory analysis of the product was performed with untrained assessors for the 9-point mixed hedonic acceptance test. The sensory evaluators, before the tests, were informed about the research objectives and methodology and consulted by means of a Free and Informed Consent. The results obtained were satisfactory, since there was a good sensorial acceptance of the liquor based on the vinagreira, making it an option for commercialization. With a good acceptance of the product in sensory aspects.